Extensive Cortical Diffusion Restriction in a 50-Year-Old Female with Hyperammonemic Encephalopathy and Status Epilepticus - Adam de Havenon; Kris French; Safdar Ansari (Case Reports in Neurological Medicine, 2014)
Comorbid hyperammonemic encephalopathy (HE) and status epilepticus (SE) leading to extensive cortical diffusion restriction (CDR) on MRI have not been previously reported. We describe a patient with HE who subsequently developed provoked SE. Sequential MRIs demonstrated a progressive CDR that involved the entire bilateral supratentorial cortex, thalami, and basal ganglia, resulting in death from cerebral edema and brain herniation. Diffuse CDR is most frequently seen after hypotension or hypoxia, which our patient did not experience. Such findings have also been described in both HE and SE (Milligan et al. (2009), Chatzikonstantinou et al. (2011), U-King-Im et al. (2011), and Bindu et al. (2009)), but not to the extent seen in our patient. Additionally, our patient had distinct radiologic features of both disease processes, suggesting a cumulative effect. The diagnosis of HE and SE in the setting of extensive CDR should not be missed and could lead to improved outcomes for two progressive, malignant, and treatable illnesses that can be easily overlooked.